Kinome profiling analysis identified Src pathway as a novel therapeutic target in combination with histone deacetylase inhibitors for cutaneous T-cell lymphoma. Issue 3 (March 2021) - Jimura, Nozomi; Fujii, Kazuyasu; Qiao, Zhiwei; Tsuchiya, Ryuto; Yoshimatsu, Yuki; Kondo, Tadashi; Kanekura, Takuro
Highlights: HDACi treatment activated the TK pathway in CTCL cell lines. The Src kinase inhibitor ponatinib enhanced HDACi-induced apoptosis. The Src pathway may be a target of combination therapy with HDACi in CTCL. Abstract: Background: Histone deacetylase inhibitors (HDACi) are used to treat patients with cutaneous T-cell lymphoma (CTCL), but they show limited efficacy. Hence, combination therapies should be explored to enhance the effectiveness of HDACis. Objective: This study was conducted to identify novel therapeutic targets that can be combined with HDACis for treating CTCL. Methods: We performed a global kinome profiling assay of three CTCL cell lines (HH, MJ, and Hut78) with three HDACis (romidepsin, vorinostat, and belinostat) using the PamChip® microarray. The three cell lines were co-treated with romidepsin and an inhibitor against the tyrosine kinase pathway. Results: Principal component analysis revealed that kinome expression patterns were mainly related to the cell origin and were not affected by the drugs. Few kinases were commonly activated by the HDACis. Most identified kinases were Src-associated molecules, such as annexin A2, embryonal Fyn-associated substrate, and progesterone receptor. Phosphorylated Src was not observed in any untreated cell lines, whereas Src phosphorylation was detected in two of the three cell lines after HDACi treatment. Ponatinib, a Src inhibitor, significantly enhanced romidepsin-induced apoptosis not only in HH, MJ, and Hut78 cells, but also in Myla and SeAx CTCL cell lines. Conclusion: The Src pathway is a possible target for combination therapy involving HDACis for CTCL.